ANALISIS VIDEO DALAM KANAL YOUTUBE 1 JOUR 1 QUESTION UNTUK KETERAMPILAN MENYIMAK TINGKAT A1 DAN A2 - Ananda Ayu Putri, - (2018)
This study explains: (1) the components of certain video to be used as a media for French listening comprehension for beginners. This analysis is using videos that can be obtained in the Youtube channel 1 Jour 1 Question, and in the assesment (2) for auditory feature, the record have a good quality and clear enough to be understood even though the speed is quite fast for beginners; (3) for visual feature the videos are interesting and fun for learners; (4) meanwhile for the grammatical and other learning objectifs, the video is suitable to be used not just for beginners but also for an advanced learners; (5) and in a good class management, this media could be used not just for listening comprehension, but also a new source of information and discussion. The aim of this study is to find a media that could provide different learning environments for learners, and so educators could find a variety of choices in using technology and media for learning. As a result, we can conclude that the videos in Youtube channel 1 Jour 1 Question can be used as a media for listening comprehension on level A1 and A2.---- Cette étude explique: (1) les contenus des certaines vidéos à utiliser comme un média de la compréhension orale pour les débutants. Cette analyse utilise des vidéos qui peuvent être obtenues sur la chaîne Youtube 1 Jour 1 Question, et dans l'évaluation (2) la fonction auditive, les enregistrements ont de bonne qualité et assez clairs à comprendre même-si la vitesse est assez rapide pour les débutants; (3) la fonction visuelle, les vidéos sont intéressantes et amusantes pour les apprenants; (4) les contenus grammaticaux et les autres objectifs d'apprentisage, les vidéos peuvent être utilisés non seulement pour les débutants, mais aussi pour les intermédiares; (5) ce média pourrait être utilisé non seulement pour l'apprentisage de compréhension orale, mais aussi pour une source d'information. Le but de cette étude est de trouver un média qui pourrait fournir une différent environnement d'apprentissage pour les apprenants, et ainsi les enseignants pourraient trouver une variété dans l'utilisation de la technologie et des médias pour l'apprentissage.